The hybrid metaheuristic scheduling model for garment manufacturing on-demand - Мoch Sаiful Umam (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
The latest technology milestone drives the fashion industry to implement on-demand production services. This study introduces a decision-making scheme in the manufacturing on-demand production scheduling of the garment industry using a hybrid metaheuristic model to meet consumer demand in the digital economy as quickly as possible. Then we conduct computational experiments based on the real-world case study and compare the hybrid metaheuristic method with existing approaches. The experimental results demonstrate that the hybrid metaheuristic approach can yield very efficient solutions to the scheduling problem; it can save production completion time by 22.6%; it shows promising performance compared to the existing methods.